TRANSFORMING WRITING INSTRUCTION: ENGAGING AND ACCESSIBLE STRATEGIES FOR UNIVERSITY-LEVEL BEGINNERS - Noviarini, Tiara (English Community Journal, 2025)
This study aims to explore and analyze engaging and easily accessible writing instruction strategies for beginner university students. Writing skills pose particular challenges for students, especially when faced with academic demands and the use of a foreign language. Conventional, monotonous teaching methods often fail to overcome psychological barriers such as anxiety and lack of motivation in writing. Through a qualitative descriptive approach using a case study of students at STIES Mitra Karya, this research identifies that interest-based strategies, the use of simple visual media, and student collaboration can enhance both motivation and writing quality. The analysis results reveal significant improvements in paragraph structure, sentence transitions, vocabulary, grammar, and writing length after implementing the new strategies. Students also demonstrate a more positive attitude toward writing activities. This study emphasizes the importance of transforming writing instruction into a fun and inclusive learning process, as well as the critical facilitative role of instructors in creating a supportive learning environment.